Taxonomia e diversidade de Encarsi no Brasil e a biologia de Bemisia tabaci biótipo B e seu parasitoide Encarsia desantisi em algodoeiro Bt e não Bt - Pessoa, Roseli [UNESP] (2015)
The Encarsia genus is one of the most diverse of Aphelinidae family and has great economic importance in the biological control of insects, especially whiteflies. Native fauna studies of species of Encarsia are of great interest for Biological Control Natural and applied within the philosophy of Integrated Pest Management. Despite its importance, the biological control of whiteflies, species diversity, taxonomy, morphology and biology of Encarsia spp. It is little known and studied in Brazil. The whitefly Bemisia tabaci biotype B, being a polyphagous kind of easy adaptation to new hosts has caused economic damage in transgenic cotton crops that has been gaining ground in modern agriculture. Despite its effectiveness in controlling caterpillars, there are still many controversies about its impact on the environment and non-target organisms this technology. The objectives to be achieved were: to propose identification key to species of Encarsia occurring in Brazil and descriptive catalog of species, study the diversity of species of Encarsia and their hosts in different plant species; study the biology and possible effects of Bt cotton tritróficos on non-target organisms. Sixteen species of Encarsia it was collected, with six new occurrences in Brazil, E. Trialeurodes Myartseva, 2007 E. elongata (Dozier, 1937), E. woolleyi Myartseva & Evans, 2008; E. albiscutellum (Girault, 1913), Howard E. variegata, 1908 and E. mineoi Viggiani, 1982, three of which have not yet reported in the Neotropical Region totaling 34 species. Considering the mega diversity of tropical fauna and flora surveys studies of species diversity are needed, as well as their hosts and their biologies. In transgenic cotton cultivars was reduced by approximately 20% adult emergence of B. tabaci biotype B, compared to their non-transgenic cultivars.In contrast, we observed a significant increase of approximately 10% emergence E. desantisi for parasitoids of host fed ...